Adhesive, adhesive sheet, and flexible copper-clad laminate
Patent Information
- Application Number
- CN202210684805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-18
- Filing Date
- 2022-06-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-06-17
AI Technical Summary
然而,专利文献10中,公开了粘接剂显示出高软化点(20~220℃)、低介电常数和低介电损耗角正切,但根本没有提及尺寸稳定性
以往,在高温下将粘接片的粘接剂层与铜箔进行层压时,会产生铜箔断裂或褶皱等缺陷,特别是,在铜箔厚度为薄至18μm以下的情况下,这种缺陷更加显著。通过使用本发明的特定的粘接剂,将粘接剂层层合在聚酰亚胺膜基材的表面上,来制作粘接片,即使在铜箔的厚度较薄的情况下,也可在较低的温度下将粘接片的粘接剂层与铜箔进行层压,可提供没有铜箔断裂或褶皱等缺陷的柔性覆铜层合板。因此,无需经过作为尺寸稳定性恶化的主要原因之一的高温高压下的层压工序,而且,由于热固化温度也为200℃以下,因此可大幅改善柔性覆铜层合板的尺寸稳定性。其结果,可提供兼具与浇铸法2层FCCL相同的特性和层压法2层FCCL以上的生产率的柔性覆铜层合板。
Smart Images

Figure QLYQS_1 
Figure 912DEST_PATH_IMAGE008 
Figure 24101DEST_PATH_IMAGE005
Abstract
Description
Technical Field
[0001] This invention relates to flexible copper clad laminates (FCCLs) for use in flexible printed wiring boards and the like, adhesives for manufacturing such flexible copper clad laminates, and adhesive sheets. Background Technology
[0002] In recent years, with the trend towards lighter, smaller, and higher-density electronic products, the demand for various printed circuit boards (PCBs) is increasing, especially for flexible PCBs. The main materials for flexible PCBs include flexible copper-clad laminates, cover films, and interlayer insulating materials (adhesive sheets). Flexible copper-clad laminates used in flexible PCBs are typically formed from various insulating materials, using flexible insulating films such as polyimide films as the substrate. They are manufactured by bonding metal foils to the surface of this substrate using various adhesives through heating / pressing.
[0003] As an adhesive for bonding copper foil to polyimide film, flexible copper-clad laminates (hereinafter also referred to as "3-layer FCCLs") using thermosetting resins such as epoxy resins or acrylic resins are employed. These thermosetting adhesives have the advantage of bonding at relatively low temperatures, but as the required properties such as heat resistance, chemical resistance, electrical reliability, dimensional stability, and thin-walled applications become increasingly stringent, 3-layer FCCLs are becoming increasingly difficult to meet. Therefore, flexible copper-clad laminates (hereinafter also referred to as "2-layer FCCLs") with the metal layer directly placed on the polyimide film or with thermoplastic polyimide used as the adhesive layer have been expanding. Compared to 3-layer FCCLs, 2-layer FCCLs are particularly superior in terms of heat resistance, dimensional stability, and electrical reliability, and also facilitate thin-walled applications.
[0004] Two-layer FCCL includes three manufacturing methods: lamination, casting, and sputtering, each with its own advantages and disadvantages.
[0005] The laminated two-layer FCCL boasts high productivity among the three methods due to its process of bonding adhesive sheets with thermoplastic polyimide (TPI) adhesive layers formed on one or both sides of a polyimide film to conductive metal foil. (Patent Documents 1, 3-5) Typically, two-layer FCCL requires high solder heat resistance for lead-free solder and dimensional stability for high-density mounting. However, because the laminated two-layer FCCL uses high-melting-point thermoplastic polyimide (TPI) as the adhesive, the lamination process must be performed at high temperatures and pressures above 300°C, which deteriorates dimensional stability after etching and heating. Various improvements have been made to enhance dimensional stability, but it remains insufficient. Furthermore, the combined use of heat-resistant protective films becomes essential to prevent copper foil breakage and wrinkling, presenting a cost challenge.
[0006] The casting-based two-layer FCCL uses a process of casting (coating) a polyimide precursor onto a conductive metal foil and then heating it to imidize it (Patent Documents 6 and 7). However, it suffers from inherent drawbacks such as low productivity and the need for large-scale equipment. To improve dimensional stability and the reliability of copper foil adhesion, a method has been developed that uses a high-adhesion polyimide with improved adhesion between the low-thermal-expansion polyimide and the copper foil, allowing for the coating of three layers onto the copper foil at any thickness ratio that matches the coefficient of thermal expansion of the cured polyimide, followed by curing. Furthermore, a wide-width continuous coating / curing process for single-sided two-layer FCCL or a high-speed / wide-width continuous lamination process for double-sided two-layer FCCL has been developed. As a result of repeated improvements, the casting-based two-layer FCCL currently exhibits the most stable properties among the three methods, but it has not yet overcome the inherent drawbacks of low productivity and the need for large-scale equipment.
[0007] Sputtering two-layer FCCL is a process that laminates a conductive metal onto a polyimide film by sputtering. Due to the ease of thinning the conductor layer and the smooth interface between the metal and the film, it is advantageous for forming fine patterns (Patent Document 2). However, because sputtering requires vacuum evaporation equipment, has high production costs and poor productivity, FCCL is also the most expensive of the three methods.
[0008] On the other hand, methods have been reported for using a film composed of a solvent-soluble polyimide resin containing a phenyl indane (dihydroindane) structure and a thermosetting resin composition containing epoxy resin as an interlayer insulating material or adhesive for multilayer substrates (Patent Documents 8 and 9). In Patent Document 8, a thermosetting resin composition is used as an interlayer insulating material for multilayer substrates with a rigid substrate such as FR-4 as the core material. In Patent Document 9, when fabricating a multilayer printed wiring board by overlapping copper foil onto a flexible copper-clad laminate as the core material, a thermosetting resin composition is used as an adhesive to bond the copper on the surface of the flexible copper-clad laminate to the copper foil; the thermosetting resin composition uses a phenyloxy resin with a glass transition temperature (Tg) of 130°C or higher. However, the adhesive in Patent Document 9 is not a material used to bond the polyimide film substrate constituting the FCCL to the copper foil. Furthermore, Patent Document 10 discloses an adhesive comprising a polyimide resin and a crosslinking agent as an adhesive for bonding a polyimide film constituting an FCCL to a copper foil. However, while Patent Document 10 discloses that the adhesive exhibits a high softening point (20–220°C), a low dielectric constant, and a low dielectric loss tangent, it makes no mention of dimensional stability.
[0009] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 6-232553; Patent Document 2: Japanese Patent Application Publication No. 2002-280684; Patent document 3: Japanese Patent Application Publication No. 2003-71982; Patent document 4: Japanese Patent Application Publication No. 2003-136631; Patent document 5: Japanese Patent Application Publication No. 2014-198385; Patent document 6: Japanese Patent Application Publication No. 2016-215651; Patent document 7: Japanese Patent Application Publication No. 2019-081379; Patent document 8: Japanese Patent Application Publication No. 2006-328214; Patent document 9: Japanese Patent Application Publication No. 2013-35881; Patent document 10: Japanese Patent Application Publication No. 2019-172989. Summary of the Invention
[0010] The problem that the invention aims to solve Of the two-layer FCCLs, from a productivity standpoint, the lamination method is superior, while from a performance standpoint, the casting method is superior. Therefore, a lamination process is needed to achieve the same characteristics as the casting method. Because the lamination temperature of the lamination process for two-layer FCCLs is as high as 300°C or more, high-heat-resistant films such as polyimide films are used in combination during lamination to eliminate defects such as copper foil breakage or wrinkling. Furthermore, due to the high-temperature lamination, dimensional stability inevitably deteriorates. Therefore, there is a need for an adhesive that can laminate the adhesive layer to the copper foil without causing such defects and provides excellent dimensional stability for FCCLs.
[0011] The present invention was made in view of the above-mentioned actual situation, and its purpose is to: develop an adhesive for flexible copper clad laminate that provides the same characteristics as casting 2-layer FCCL and the productivity of lamination 2-layer FCCL, while having no defects such as copper foil breakage or wrinkles and excellent dimensional stability; and to provide adhesive sheets and lamination flexible copper clad laminates (hereinafter also referred to as "2.2-layer FCCL") manufactured using the adhesive.
[0012] Methods for solving problems Through repeated and in-depth research, the inventors discovered that in the lamination method of two-layer FCCL, by changing the thermoplastic polyimide (TPI) used as the adhesive to a thermosetting adhesive comprising a polymer blend (polymer alloy) containing a specific solvent-soluble polyimide, a phenoxy resin with a glass transition temperature (Tg) below 120°C, an epoxy resin, and an epoxy resin curing agent, the dimensional stability, which is an improvement point in the properties of the lamination method of two-layer FCCL, can be improved. The same properties as the casting method of two-layer FCCL can be achieved, while eliminating defects such as copper foil breakage or wrinkles during lamination, thus completing the present invention.
[0013] That is, the present invention provides an adhesive for bonding a polyimide film substrate constituting a flexible copper-clad laminate to a copper foil, the adhesive comprising: a solvent-soluble polyimide having repeating units represented by the following general formula [I], a phenoxy resin with a glass transition temperature (Tg) of 120°C or less, an epoxy resin, and an epoxy resin curing agent. In the formula, Z is an aromatic or alicyclic tetracarboxylic dianhydride residue, and Ar is an aromatic diamine residue with a phenylindanate structure.
[0014] In addition, the present invention provides an adhesive sheet, which is an adhesive sheet for flexible copper-clad laminate formed by laminating an adhesive layer for bonding copper foil onto one or both sides of a polyimide film substrate constituting a flexible copper-clad laminate, wherein the adhesive layer contains the adhesive of the present invention.
[0015] In addition, the present invention provides a flexible copper-clad laminate, which is formed by sequentially laminating an adhesive layer and a copper foil on one or both sides of a polyimide film substrate, wherein the adhesive layer contains the adhesive of the present invention.
[0016] Furthermore, the present invention provides a method for manufacturing the flexible copper-clad laminate of the present invention, the method comprising: pressing a copper foil laminate onto the adhesive sheet of the present invention at a temperature of 70 to 120°C, and then curing the adhesive layer at a temperature below 200°C.
[0017] Invention Effects Previously, laminating the adhesive layer of an adhesive sheet to copper foil at high temperatures resulted in defects such as copper foil breakage or wrinkling, especially when the copper foil thickness was less than 18 μm. By using the specific adhesive of this invention, the adhesive layer is laminated onto the surface of a polyimide film substrate to create the adhesive sheet. Even with thin copper foil, the adhesive layer of the adhesive sheet can be laminated to the copper foil at a lower temperature, providing a flexible copper-clad laminate without defects such as copper foil breakage or wrinkling. Therefore, the high-temperature, high-pressure lamination process, a major cause of dimensional instability, is eliminated. Furthermore, since the thermosetting temperature is below 200°C, the dimensional stability of the flexible copper-clad laminate is significantly improved. As a result, a flexible copper-clad laminate combining the same characteristics as a cast 2-layer FCCL with the higher productivity of a laminated 2-layer FCCL can be provided. Detailed Implementation
[0018] The adhesive for flexible copper-clad laminates of the present invention is an adhesive for bonding a polyimide film substrate constituting a flexible copper-clad laminate to a copper foil. The adhesive contains: a solvent-soluble polyimide having repeating units represented by the following general formula [I], a phenoxy resin with a Tg of 120°C or less, an epoxy resin, and an epoxy resin curing agent. In the above general formula, Z is an aromatic or alicyclic tetracarboxylic dianhydride residue, and Ar is an aromatic diamine residue with a phenylindanate structure.
[0019] (Solvent-soluble polyimide) In the repeating unit represented by the above general formula [I] of the solvent-soluble polyimide in the present invention, there are no particular limitations on the aromatic tetracarboxylic dianhydride used to introduce the aromatic tetracarboxylic dianhydride residue represented by Z into the polyimide, but benzophenone tetracarboxylic dianhydride or biphenyl tetracarboxylic dianhydride is preferred.
[0020] Examples of alicyclic tetracarboxylic dianhydrides used to introduce the alicyclic tetracarboxylic dianhydride residue represented by Z into polyimides include: bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, norcamphene-2-spiro-α-cycloalkanone-α'-spiro-2''-norcamphene-5,5'',6,6''-tetracarboxylic dianhydride, and 1,2,3,4-cyclobutanetetracarboxylic dianhydride. 1,2,3,4-Cyclopentanetetracarboxylic dianhydride, 1,2,4,5-Cyclohexanetetracarboxylic dianhydride, 2,3,5-Tricarboxycyclopentylacetic dianhydride, 3,5,6-Tricarboxynorbornene-2-acetic dianhydride, 2,3,4,5-Tetrahydrofurantetracarboxylic dianhydride, 1,3,3a,4,5,9b-Hexahydro-5-(Tetrahydro-2,5-dioxo-3-furanyl)-naphtho [1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-5-methyl-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]-furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-8 ...furan-1,3-dione, 1,3,3a,4,5,9b-furan-1,3-dione, 1,3,3a,4,5,9b-furan-1,3-dione, 1,3,3a,4,5,9b-furan-1,3- [c]-furan-1,3-dione, 5-(2,5-dioxotetrahydrofuranyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, bicyclo[2,2,2]-oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2,2,1]-heptane-2,3,5,6-tetracarboxylic dianhydride, and decahydrodimethylbridged naphthalene-2,3,6,7-tetracarboxylic dianhydride, etc.
[0021] The phenyl indane structure of the aromatic diamine residue represented by Ar refers to a structure obtained by substituting a phenyl group with a substituent on the indane backbone described below. Examples of substituents include halogen atoms or alkyl groups having 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms. The aromatic diamine residue (Ar) with the phenyl indane structure is preferably a diamine residue with a structure obtained by substituting a phenyl group with a substituent at the 1 or 2 position of the indane backbone described below, wherein the diamine residue represented by the following general formula [II] is preferred.
[0022] In general formula [II], R1, R2 and R3 each independently represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, preferably an alkyl group having 1 to 3 carbon atoms. In addition, each of R4 and each of R5 independently represent a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, preferably an alkyl group having 1 to 3 carbon atoms.
[0023] Examples of aromatic diamines used to introduce aromatic diamine residues (Ar) having a phenylindene structure into polyimides include: 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene, 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene, 5-amino-6-methyl-1-(3'-amino-4'-methylphenyl)-1,3,3-trimethylindene, and 5-amino-1-(4'-amino-Ph',Ph'-dichloro... Ph-phenyl indene, Ph-dichloro-1,3,3-trimethyl indene, 6-amino-1-(4'-amino-Ph', Ph'-dichloro-phenyl)-Ph, Ph-dichloro-1,3,3-trimethyl indene, 4-amino-6-methyl-1-(3'-amino-4'-methyl-phenyl)-1,3,3-trimethyl indene, Ph-amino-1-(Ph'-amino-2',4'-dimethylphenyl)-1,3,3,4,6-pentamethyl indene, etc. In the above examples, Ph and Ph' represent unspecified positions on the benzene ring within the phenyl indene structure.
[0024] From the viewpoint of improving the compatibility between solvent-soluble polyimide and epoxy resin, the content of the aromatic diamine component (Ar component) having a phenyl indane structure constituting the solvent-soluble polyimide is 50 mol% or more, preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, and particularly preferably 90 mol% or more of the total diamine component.
[0025] Solvent-soluble polyimides can be block-lock copolymers having a repeating unit other than the repeating unit represented by the general formula [I] above, or they can have repeating units having other aromatic diamine residues, aliphatic diamine residues, or alicyclic diamine residues, or diamine residues of diaminopolysiloxane in the main chain. Examples of diamines used to introduce diamine residues of diaminopolysiloxane in the main chain into polyimides include: α,ω-bis(2-aminoethyl)polydimethylsiloxane, α,ω-bis(3-aminopropyl)polydimethylsiloxane, α,ω-bis(4-aminophenyl)polydimethylsiloxane, α,ω-bis(4-amino-3-methylphenyl)polydimethylsiloxane, α,ω-bis(3-aminopropyl)polydiphenylsiloxane, α,ω-bis(4-aminobutyl)polydimethylsiloxane, etc.
[0026] Solvent-soluble polyimides having repeating units represented by the above general formula (I) are obtained by dehydration condensation reaction of an aromatic or alicyclic tetracarboxylic dianhydride with an aromatic diamine having a phenylindenman structure.
[0027] Solvent-soluble polyimides can be synthesized using well-known methods without particular limitations. Approximately equal amounts of the aforementioned tetracarboxylic dianhydride and aromatic diamine are reacted in an organic polar solvent in the presence of a catalyst and a dehydrating agent at 160–200°C for several hours to synthesize solvent-soluble polyimides. Suitable organic polar solvents include N-methylpyrrolidone (NMP), γ-butyrolactone, N,N'-dimethylacetamide, N,N'-dimethylformamide, dimethyl sulfoxide, tetramethylurea, and tetrahydrothiophene-1,1-oxide.
[0028] Solvent-soluble polyimides are preferably block copolymers, which can be synthesized by block copolymerization. For example, they can be manufactured by a two-step sequential addition reaction, in which a polyimide oligomer is synthesized from a tetracarboxylic dianhydride and an aromatic diamine in the first step, and then a block copolymer polyimide is prepared by further adding a tetracarboxylic dianhydride and / or an aromatic diamine in the second step for polycondensation.
[0029] As a catalyst for block copolymerization, the dehydration imidization reaction can be promoted by using a two-component acid-base catalyst that utilizes the lactone equilibrium reaction. Specifically, a two-component catalyst of γ-pentanolide and pyridine or N-methylmorpholine is used. As shown in the following formula, water is generated as imidization proceeds, and the generated water participates in the lactone equilibrium, thus acting as an acid-base catalyst and exhibiting catalytic activity.
[0030] The water generated by the imidization reaction is removed from the system by azeotropic reaction with a dehydrating agent such as toluene or xylene, which coexists in a polar solvent. Upon completion of the reaction, the water in the solution is removed, and the acid-base catalyst, γ-valerolactone and pyridine or N-methylmorpholine, is removed from the system. This process yields a high-purity polyimide solution.
[0031] As other two-component catalysts, oxalic acid or malonic acid and pyridine or N-methylmorpholine can be used. In a reaction solution at 160–200 °C, oxalate or malonic acid acts as an acid catalyst to promote the imidization reaction. A catalytic amount of oxalic acid or malonic acid remains in the resulting polyimide solvent. After coating the polyimide solution onto a substrate and heating it to above 200 °C, during the solvent removal process to form a film, the oxalic acid or malonic acid remaining in the polyimide undergoes pyrolysis as shown in the following formula and is removed from the system as a gas.
[0032] The above methods can yield high-purity solvent-soluble polyimide. Compared with valerol-pyridine catalysts, oxalic acid-pyridine catalysts are more active and can generate high molecular weight polyimide in a short time.
[0033] The molecular weight of the synthesized solvent-soluble polyimide, expressed as a weight-average molecular weight (Mw) converted from polystyrene, is preferably between 10,000 and 400,000. When the molecular weight of the solvent-soluble polyimide is within this range, good solvent solubility, film properties, and insulation are achieved, and therefore it is preferred.
[0034] The term "solvent solubility" in this invention refers to the organic polar solvents used in the synthesis of polyimide and the solvents used in the adhesive compositions described later, meaning that a solution of polyimide with a solid content of 20% by weight can be prepared using these solvents. Examples of solvents include NMP, γ-butyrolactone, DMF, DMAC, etc. The synthesized polyimide can be used in the aforementioned organic polar solvents or the solvents used in the adhesive compositions described later, in a dissolved solution state, for example, with a solid content of 10 to 30% by weight.
[0035] Furthermore, since the solvent-soluble polyimide of the present invention is a fully imidized polyimide, no high-temperature heat treatment for imidization is required after the adhesive is applied to the polyimide film substrate. Therefore, compared to polyamic acid (a polyimide precursor), which requires high-temperature heat treatment (above 300°C) for imidization after the adhesive is applied to the polyimide film substrate, it has the advantage of providing flexible copper-clad laminates with high dimensional stability.
[0036] (Epoxy resin) The epoxy resin used in this invention is not particularly limited, but epoxy resins with a rigid structure having two or more glycidyl groups are preferred. The molecular weight (Mw) of the epoxy resin is typically 200 to 2,000, preferably 280 to 1,000. Biphenyl-type epoxy resins, naphthalene-type epoxy resins, dicyclopentadiene-type epoxy resins, bisphenol A-type epoxy resins, etc., are particularly preferred, and can be used alone or in combination of two or more.
[0037] The epoxy resin in this invention refers to an epoxy resin that is compatible with solvent-soluble polyimide, and is a resin that can modify the properties of solvent-soluble polyimide. Since epoxy resin is compatible with solvent-soluble polyimide resin, a compatible polymer blend is generated by mixing epoxy resin and solvent-soluble polyimide.
[0038] (Epoxy resin curing agent) As the curing agent in this invention, any resin that cures the epoxy resin is acceptable, and there are no particular limitations. Examples include phenolic varnish phenolic resins or resins having naphthalene and aralkyl structures. Examples of phenolic varnish phenolic resins include: phenol phenolic varnish resins, cresol phenolic varnish resins, benzoguanamine-modified bisphenol A type phenolic varnish resins as triazine-modified phenolic varnish resins, benzoguanamine-modified cresol phenolic varnish type phenolic resins, benzoguanamine-modified phenol phenolic varnish type phenolic resins, melamine-modified bisphenol A type phenolic varnish resins, melamine-modified cresol phenolic varnish type phenolic resins, and melamine-modified phenol phenolic varnish type phenolic resins. Examples of resins having naphthalene and aralkyl structures include: 1-naphthol aralkyl resins, 2-naphthol aralkyl resins, and 1,6-naphthyldiol aralkyl resins.
[0039] The amount of curing agent used, relative to epoxy resin, can be 0.5 equivalents or more and 1.2 equivalents or less, based on hydroxyl equivalents. If the amount of curing agent used is less than 0.5 equivalents, a suitable Tg may not be obtained; therefore, 0.5 equivalents or more is preferred, but 0.6 equivalents or more is more preferred. Furthermore, if the amount of curing agent used exceeds 1.2 equivalents, the water absorption properties of the resin may decrease; therefore, 1.2 equivalents or less is preferred, but 1.0 equivalents or less is more preferred.
[0040] Aromatic amine resins can also be used as curing agents. As long as the aromatic amine resin can cure the epoxy resin, there are no particular limitations; examples include: 4,4'-diaminodiphenyl sulfone, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, trimethylene bis(4-aminobenzoate), polyoxybutylene-di-p-aminobenzoate, 3, 3'-Dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 9,9'-bis(4-aminophenyl)fluorene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, etc., can be used alone or in combination of two or more.
[0041] There is no limitation on the amount of aromatic amine resin used, but the most suitable amount of aromatic amine compound when the molar amount of epoxy resin is 1 is 0.3 to 1.5 moles. By using an amount of aromatic amine resin (total moles) of 0.3 or more, an adhesive layer with a suitable coefficient of thermal expansion can be easily obtained. From this viewpoint, it is further preferred that the amount of aromatic amine resin used (total moles) is 0.4 or more. Furthermore, even if the amount of aromatic amine resin used (total moles) is 1.5 or less, an adhesive layer with a suitable coefficient of thermal expansion can be easily obtained. From this viewpoint, it is further preferred that the amount of aromatic amine resin used is 1.2 or less.
[0042] (Phenoxy resin) The phenoxy resin in this invention is a phenoxy resin with a glass transition temperature (Tg) of less than 120°C. Specifically, a phenoxy resin with a molecular weight (Mw) of more than 10,000 is suitable. As a resin skeleton, considering adhesion, BPA type, BPA / BPF type, BPA / BPS type, BP / BPS type, etc. are suitable. Commercially available products include, for example: JER1256 (weight-average molecular weight (Mw) 48,000, glass transition temperature (Tg) 95°C, manufactured by Mitsubishi Chemical Corporation), PKHJ (Mw 57,000, Tg 98°C, manufactured by Gabriel Phenoxies Corporation), PKHH (Mw 52,000, Tg 92°C, manufactured by Gabriel Phenoxies Corporation), PKFE (Mw 60,000, Tg 98°C, manufactured by Gabriel Phenoxies Corporation), FX-310 (Mw 45,000, Tg 110°C, manufactured by Nippon Steel Epoxy Manufacturing Co., Ltd.), etc.
[0043] By using phenoxy resins with a glass transition temperature (Tg) below 120°C, similar to solvent-soluble polyimide resins, the adhesive layer formed by the adhesive is endowed with flexibility and adhesion, while allowing the adhesive layer to be bonded to the copper foil at a lower temperature. To prevent defects such as copper foil breakage or wrinkling during lamination of the adhesive layer to the copper foil, and to ensure that the Tg of the adhesive layer made by the adhesive is within the optimal range described later, the Tg of the phenoxy resin is preferably 80–115°C, more preferably 85–113°C, and most preferably 90–110°C. The Tg of the phenoxy resin can be measured according to IPC-TM-650-2.4.24.3.
[0044] The weight ratio of solvent-soluble polyimide resin (solid component) to phenoxy resin in the adhesive composition is typically 1:1.2 to 12.0, preferably 1:1.3 to 10.0, more preferably 1:1.4 to 9.5, and even more preferably 1:1.5 to 9.0.
[0045] The total content (by weight%) of solvent-soluble polyimide resin, phenoxy resin, epoxy resin, and epoxy resin curing agent in the adhesive composition is typically 10 to 50% by weight. If the total content of solvent-soluble polyimide resin and phenoxy resin is less than 10% by weight, the adhesive strength and flexibility of the adhesive layer formed by the adhesive composition may be low. Therefore, relative to the total weight of epoxy resin and epoxy resin curing agent, it is preferable to be 15% by weight or more, and more preferably 20% by weight or more. Furthermore, if the total content of solvent-soluble polyimide resin and phenoxy resin exceeds 50% by weight, the tensile strength of the film may be reduced. Therefore, relative to the total weight of epoxy resin and epoxy resin curing agent, it is preferable to be 45% by weight or less, and more preferably 40% by weight or less.
[0046] In addition to the solvent-soluble polyimide, epoxy resin, curing agent and phenoxy resin mentioned above, the adhesive of the present invention may also be an adhesive composition containing curing accelerator, flame retardant and the like.
[0047] (Curing accelerator) In the adhesive of the present invention, curing accelerators may be used in combination as needed. Various common curing accelerators, such as imidazoles, can be used as curing accelerators. The selection can be made primarily from the viewpoint of reaction rate or pot life.
[0048] (Flame retardant) In the adhesive of the present invention, flame retardants may be added as needed to impart flame retardancy. As halogen-free flame retardants, condensed phosphate esters, phosphazenes, polyphosphates, HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) derivatives, etc., may be used.
[0049] A resin varnish with a resin solid content of 20-60% by weight is prepared by adding a solvent to a mixture obtained by mixing epoxy resin, curing agent, solvent-soluble polyimide and phenoxy resin, and the above-mentioned resin components as needed, thereby producing an adhesive (composition).
[0050] There are no particular limitations on the solvents that can be used in the adhesive compositions of the present invention. It is preferred to combine high-boiling-point solvents such as NMP, γ-butyrolactone, methyl benzoate, diethylene glycol monomethyl ether acetate or diethylene glycol monomethyl ether acetate with medium / low-boiling-point solvents such as cyclohexanone or MEK (methyl ethyl ketone).
[0051] (Tensile modulus and Tg of adhesive film) The adhesive (composition) of the present invention is an adhesive that has a tensile modulus of 1 to 10.0 GPa and a Tg (glass transition temperature) of 120 to 190°C by heating and curing a semi-cured film made of the adhesive at 180°C for 90 minutes.
[0052] The film for determining tensile modulus and Tg was prepared as follows: A resin varnish prepared as described above was applied to the glossy surface of an 18 μm electrolytic copper foil using a bar coater and dried at 150°C to produce a semi-cured (B-state) copper foil with adhesive (adhesive thickness: approximately 21 μm). The volatile content of the solvent was adjusted to 0.6 wt%. The glossy surface of the 18 μm electrolytic copper foil was stacked on the surface of the adhesive sheet of the copper foil with adhesive, and the film was placed in a vacuum press and heated / pressurized at 180°C for 90 minutes at 1 MPa (vacuum degree 5 torr) to form the film. Then, the tensile modulus and Tg were measured for the approximately 20 μm adhesive film obtained by etching the entire surface of the copper foil. The tensile modulus was measured according to IPC-TM-650-2.4.18.3, and the Tg was measured according to IPC-TM-650-2.4.24.3.
[0053] Here, the tensile modulus is mainly related to the dimensional stability of the FCCL, but it is also related to warping or undulation of the printed wiring board. Warping is caused by a mismatch, particularly in the tensile modulus or coefficient of thermal expansion, between the polyimide film used as the core material and the adhesive layer. Since this mismatch occurs even in double-sided symmetrical adhesive sheets, it is desirable for the tensile modulus and coefficient of thermal expansion to be equal between the polyimide film and the adhesive layer. However, achieving this is a very difficult task for solvent-soluble polyimide resins. As a solution, setting the tensile modulus of the adhesive layer to be lower than that of the core polyimide film substrate is effective. If the tensile modulus of the adhesive layer is higher than that of the core polyimide film substrate, the thermal strain of the core polyimide film substrate increases, and the rate of dimensional change after heating increases. In addition, if the tensile modulus of the adhesive layer is lower than 1 GPa, undulation of the FCCL is more likely to occur. The tensile modulus is preferably in the range of 1.1 to 5.0 GPa, more preferably in the range of 1.2 to 3.0 GPa, and particularly preferably in the range of 1.2 to 2.5 GPa.
[0054] In addition, regarding the Tg (glass transition temperature) of the film made of the adhesive, it is preferably 125 to 185°C, and more preferably 130 to 180°C.
[0055] (Adhesive sheet) By subjecting the adhesive (composition) of the present invention to a B-stage on one or both sides of a polyimide film substrate to a semi-cured state (B-state), an adhesive sheet for a 2.2-layer FCCL laminate can be obtained. Specifically, as described above, a resin varnish prepared by diluting the adhesive (composition) of the present invention with a suitable mixed organic solvent such as NMP / MEK is applied to one or both sides of a polyimide film substrate, which serves as the core material, using a gravure coating machine or a film die-coating machine. In the present invention, in order to achieve the same dimensional stability as a 2-layer FCCL cast by casting, the coating thickness, coating temperature, and thermosetting temperature of the adhesive layer are preferably within the following specific ranges.
[0056] The coating thickness of the adhesive layer needs to be at least the minimum thickness of the rough surface of the copper foil to be laminated, and specifically, preferably a thickness of Rz (measured according to JIS B 0601-2001) or higher. This coating thickness also has a significant impact on dimensional stability; therefore, in addition to this condition, it is also preferable that the thickness of the adhesive layer on one side is less than 20%, preferably less than 15%, and more preferably less than 13% of the thickness of the core polyimide film. The thickness of the adhesive layer of the adhesive sheet preferably satisfies both of the above conditions, but as an absolute value of the thickness, it is preferably 1.6 to 4.0 μm, more preferably 2.0 to 3.5 μm, and particularly preferably 2.5 to 2.9 μm. By setting the thickness of the adhesive layer within this range, the difference in physical properties (mainly tensile modulus and coefficient of thermal expansion) between the adhesive layer and the core polyimide film is not reflected in the physical properties of the FCCL as a composite film, thus maintaining the adhesive properties. In addition, when the adhesive sheet is heated and cured at 180°C for 90 minutes using a dryer, it is preferable that the thickness of the adhesive layer of the adhesive sheet is 1.5 to 3.5 μm.
[0057] By setting the tensile modulus and Tg of the film made from the adhesive (composition) of the present invention within the specific ranges described above, and by setting the thickness of the adhesive layer of the adhesive sheet to 1.6 to 4.0 μm, preferably 1.8 to 2.9 μm, the dimensional stability of the FCCL as a composite layer film can be made almost equal to that of the core polyimide film. Thus, adhesive sheets and laminated 2.2-layer FCCLs with the same properties as casting 2-layer FCCLs and superior productivity compared to lamination 2-layer FCCLs can be provided. Furthermore, by achieving the above conditions, warping caused by the inconsistency of the coefficients of thermal expansion of single-sided 2-layer FCCLs can be prevented, thus suppressing warping without relying on the currently widely used TPI bilaterally symmetrical structure.
[0058] Since the coating temperature of the adhesive layer (including the drying temperature after coating) also contributes to the thermal strain of the FCCL, the coating temperature is preferably below 150°C.
[0059] Flexible copper clad laminate (FCCL) After laminating (bonding) the copper foil onto the surface of the adhesive layer of the adhesive sheet prepared as described above, the adhesive layer is cured, thereby producing a 2.2-layer flexible copper-clad laminate (FCCL). The lamination of the adhesive layer of the adhesive sheet to the copper foil can be performed using a laminator at 70–120°C, preferably 75–115°C, and more preferably 80–110°C. By laminating at this relatively low temperature, a flexible copper-clad laminate without defects such as copper foil breakage or wrinkles can be produced. The thickness of the copper foil is typically 1.5–20 μm, preferably 5–18 μm. The curing temperature of the adhesive layer, which is the largest factor in thermal strain, is preferably below 200°C, more preferably below 195°C, particularly preferably below 190°C, preferably above 150°C, and more preferably above 160°C.
[0060] The above operations are used to create the bonding sheet and FCCL, thereby making the dimensional change rate after etching and heating equal to that of the two-layer FCCL cast by casting.
[0061] One of the main factors contributing to the deterioration of dimensional stability after etching and heating in conventional two-layer FCCL lamination is deformation that occurs during the lamination process with copper foil at high temperatures and pressures above 300°C. In this invention, by using an adhesive comprising a polymer blend of a specific solvent-soluble polyimide as a thermosetting resin, phenoxy resin with a Tg below 120°C, epoxy resin, and epoxy resin curing agent, copper foil lamination can be performed at lower temperatures without copper foil breakage or wrinkling. Furthermore, thermosetting can be performed below 200°C, reducing deformation occurring in each individual process and significantly improving dimensional shrinkage. Example
[0062] The present invention will now be described in detail based on embodiments. The present invention may be modified in various other ways and is not limited to the embodiments described below.
[0063] 1. Synthesis of solvent-soluble polyimide resins (Synthesis Example 1) A glass, separable three-necked flask was equipped with a stirrer, a nitrogen inlet tube, and a cooling tube with a moisture receiver. 58.84 g (0.2 mol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride (hereinafter referred to as BPDA), 26.64 g (0.1 mol) of 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene (an aromatic diamine containing a phenylindene structure), 1.5 g (0.015 mol) of valerate, 2.4 g (0.03 mol) of pyridine, 200 g of NMP, and 30 g of toluene were added. The mixture was stirred at 200 rpm for 30 minutes at room temperature under a nitrogen atmosphere, then heated to 180 °C and stirred for 1 hour. During the reaction, the toluene-water azeotrope was removed.
[0064] After cooling to room temperature, 44.13 g (0.15 mol) of BPDA, 66.60 g (0.25 mol) of 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene, 360 g of NMP, and 90 g of toluene were added. The mixture was stirred at room temperature for 30 minutes, then heated to 180 °C and stirred for 1 hour. The azeotropic reflux of water-toluene was removed from the system while the mixture was stirred at 180 °C for 2 hours and 30 minutes to terminate the reaction. The product was diluted with γ-butyrolactone to obtain a block copolymer polyimide solution with a solid content of 20% by weight.
[0065] (Synthesis Example 2) A glass, separable three-necked flask was equipped with a stirrer, a nitrogen inlet tube, and a cooling tube with a moisture receiver. 64.45 g (0.2 mol) of 3,4,3',4'-benzophenone tetracarboxylic dianhydride (hereinafter referred to as BTDA), 26.64 g (0.1 mol) of 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene (an aromatic diamine containing a phenylindene structure), 1.5 g (0.015 mol) of valproic acid, 2.4 g (0.03 mol) of pyridine, 200 g of NMP, and 30 g of toluene were added. The mixture was stirred at 200 rpm for 30 minutes at room temperature under a nitrogen atmosphere, then heated to 180 °C and stirred for 1 hour. During the reaction, the toluene-water azeotrope was removed.
[0066] After cooling to room temperature, 48.33 g (0.15 mol) of BTDA, 66.60 g (0.25 mol) of 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene, 360 g of NMP, and 90 g of toluene were added. The mixture was stirred at room temperature for 30 minutes, then heated to 180 °C and stirred for 1 hour. The azeotropic reflux of water-toluene was removed from the system while the mixture was stirred at 180 °C for 2 hours and 30 minutes to terminate the reaction. The resulting product was diluted with γ-butyrolactone to obtain a block copolymer polyimide solution with a solid content of 20% by weight.
[0067] (Synthesis Example 3) A glass, separable three-necked flask was equipped with a stirrer, a nitrogen inlet tube, and a cooling tube with a moisture receiver. 64.45 g (0.2 mol) of 3,4,3',4'-benzophenone tetracarboxylic dianhydride (hereinafter referred to as BTDA), 20.02 g (0.1 mol) of 4,4'-diaminodiphenyl ether, 1.5 g (0.015 mol) of valproic acid, 2.4 g (0.03 mol) of pyridine, 200 g of NMP, and 30 g of toluene were added. The mixture was stirred at 200 rpm for 30 minutes at room temperature under a nitrogen atmosphere, then heated to 180 °C and stirred for 1 hour. The toluene-water azeotrope was removed during the reaction.
[0068] After cooling to room temperature, 48.33 g (0.15 mol) of BTDA, 66.60 g (0.25 mol) of 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene, 360 g of NMP, and 90 g of toluene were added. The mixture was stirred at room temperature for 30 minutes, then heated to 180 °C and stirred for 1 hour. The azeotropic reflux of water-toluene was removed from the system while the mixture was stirred at 180 °C for 2 hours and 30 minutes to terminate the reaction. The product was diluted with γ-butyrolactone to obtain a block copolymer polyimide solution with a solid content of 20% by weight.
[0069] (Synthesis Example 4) A glass, separable three-necked flask was equipped with a stirrer, a nitrogen inlet tube, and a cooling tube with a moisture receiver. 64.45 g (0.2 mol) of 3,4,3',4'-benzophenone tetracarboxylic dianhydride (hereinafter referred to as BTDA), 15.98 g (0.06 mol) of 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene, 9.94 g (0.04 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 1.5 g (0.015 mol) of valerate, 2.4 g (0.03 mol) of pyridine, 200 g of NMP, and 30 g of toluene were added. The mixture was stirred at room temperature for 30 minutes, then heated to 180°C and stirred for 1 hour. The toluene-water azeotrope was removed during the reaction.
[0070] After cooling to room temperature, 48.33 g (0.15 mol) of BTDA, 66.60 g (0.25 mol) of 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindene, 360 g of NMP, and 90 g of toluene were added. The mixture was stirred at room temperature for 30 minutes, then heated to 180 °C and stirred for 1 hour. The azeotropic reflux of water-toluene was removed from the system while the mixture was stirred at 180 °C for 2 hours and 30 minutes to terminate the reaction. The product was diluted with γ-butyrolactone to obtain a block copolymer polyimide solution with a solid content of 20% by weight.
[0071] 2. Preparation of adhesive composition, fabrication of adhesive sheets and FCCL (Example 1) A resin varnish with a resin solid content of 40% by weight was prepared by adding a mixed solvent of γ-butyrolactone / cyclohexanone as a solvent to a mixture consisting of 347 parts by weight of dicyclopentadiene-type epoxy resin "HP-7200H" (manufactured by DIC Corporation, epoxy equivalent 283, resin solid content 80% by weight), 183 parts by weight of melamine-modified cresol phenolic varnish resin "EXB-9854" (manufactured by DIC Corporation, hydroxyl value 151, resin solid content 80% by weight), 290 parts by weight of soluble polyimide resin (synthesis example 1, resin solid content 20% by weight), 91 parts by weight of phenoxy resin "jER1256" (manufactured by Mitsubishi Chemical Corporation, Mw≈48,000, Tg 95℃, resin solid content 100% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazolium.
[0072] (Example 2) A resin varnish with a resin solid content of 40% by weight was prepared by adding a mixed solvent of γ-butyrolactone / cyclohexanone as a solvent to a mixture consisting of 337 parts by weight of biphenyl-type epoxy resin "NC-3000H" (manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 275, resin solid content 80% by weight), 202 parts by weight of melamine-modified phenolic varnish resin "LA-7054" (manufactured by DIC Co., Ltd., hydroxyl value 125, resin solid content 60% by weight), 98 parts by weight of soluble polyimide resin (synthesis example 2, resin solid content 20% by weight), 170 parts by weight of phenoxy resin "jER1256" (manufactured by Mitsubishi Chemical Co., Ltd., Mw≈48,000, Tg 95℃, resin solid content 100% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazolium.
[0073] (Example 3) A resin varnish with a resin solid content of 40% by weight was prepared by adding γ-butyrolactone / cyclohexanone mixed solvent as a solvent to a mixture consisting of 349 parts by weight of naphthol aralkyl type epoxy resin "ESN-165" (manufactured by Nippon Steel Epoxy Co., Ltd., epoxy equivalent 265, resin solid content 80% by weight), 177 parts by weight of melamine-modified phenolic varnish resin "LA-7054" (manufactured by DIC Co., Ltd., hydroxyl value 125, resin solid content 60% by weight), 290 parts by weight of soluble polyimide resin (synthesis example 3, resin solid content 20% by weight), 91 parts by weight of phenoxy resin "jER1256" (manufactured by Mitsubishi Chemical Co., Ltd., Mw≈48,000, Tg 95℃, resin solid content 100% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazolium.
[0074] (Example 4) A resin varnish with a resin solid content of 40% by weight was prepared by adding a γ-butyrolactone / cyclohexanone mixed solvent as a solvent to a mixture consisting of 337 parts by weight of biphenyl-type epoxy resin "NC-3000H" (manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 275, resin solid content 80% by weight), 202 parts by weight of melamine-modified phenolic varnish resin "LA-7054" (manufactured by DIC Co., Ltd., hydroxyl value 125, resin solid content 60% by weight), 98 parts by weight of soluble polyimide resin (synthesis example 1, resin solid content 20% by weight), 170 parts by weight of phenoxy resin "FX-310" (manufactured by Nippon Steel Epoxy Manufacturing Co., Ltd., Mw≈45,000, Tg 110℃, resin solid content 100% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazole.
[0075] (Example 5) A resin varnish with a resin solid content of 40% by weight was prepared by adding a γ-butyrolactone / cyclohexanone mixed solvent as a solvent to a mixture consisting of 372 parts by weight of dicyclopentadiene-type epoxy resin "HP-7200H" (manufactured by DIC Corporation, epoxy equivalent 283, resin solid content 80% by weight), 128 parts by weight of aromatic amine "Elastomer 250P" (manufactured by Kumiai Chemical Industry Co., Ltd., MW=488, resin solid content 100% by weight), 290 parts by weight of soluble polyimide resin (synthesis example 4, resin solid content 20% by weight), 91 parts by weight of phenoxy resin "jER1256" (manufactured by Mitsubishi Chemical Co., Ltd., Mw≈48,000, Tg 95°C, resin solid content 100% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazolium.
[0076] (Example 6) A resin varnish with a resin solid content of 40% by weight was prepared by adding a mixed solvent of γ-butyrolactone / cyclohexanone as a solvent to a mixture consisting of 372 parts by weight of dicyclopentadiene-type epoxy resin "HP-7200H" (manufactured by DIC Corporation, epoxy equivalent 283, resin solid content 80% by weight), 128 parts by weight of aromatic amine "Elastomer 250P" (manufactured by Kumiai Chemical Industry Co., Ltd., MW=488, resin solid content 100% by weight), 98 parts by weight of soluble polyimide resin (synthesis example 3, resin solid content 20% by weight), 170 parts by weight of phenoxy resin "FX-310" (manufactured by Nippon Steel Epoxy Manufacturing Co., Ltd., Mw≈45,000, Tg 110℃, resin solid content 100% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazolium.
[0077] The resin varnish prepared in Examples 1-6 was diluted to a solid content of 20% and coated onto a 20μm polyimide film (Kapton EN) using a gravure coating machine. The film was then dried at 150°C to produce a double-sided coated adhesive sheet in state B (single-sided film thickness: 2.8μm). The volatile content was adjusted to 0.6wt%. A 12μm copper foil with an Rz = 1.8μm was laminated onto both sides of the adhesive sheet at lamination temperatures of 110°C or 100°C using a laminator. The adhesive layer was then heated to 180°C for 90 minutes using a dryer to cure the adhesive layer, thus producing a double-sided copper foil FCCL. Similarly, the resin varnishes of each example were diluted to a solids content of 20% and coated onto a 20μm polyimide film (Kapton (registered trademark) EN) using a gravure coating machine. The film was then dried at 150°C to produce a single-sided coated adhesive sheet in state B (single-sided film thickness: 2.8μm). The volatile content was adjusted to 0.6wt%. A 12μm copper foil with an Rz = 1.8μm was laminated onto one side of the adhesive sheet using a laminator at a lamination temperature of 110°C or 100°C. The adhesive layer was then cured by heating at 180°C for 90 minutes using a dryer, thus producing a single-sided copper foil FCCL.
[0078] (Comparative Example 1) A resin varnish with a resin solid content of 40% by weight was prepared by adding a mixed solvent of γ-butyrolactone / cyclohexanone as a solvent to a mixture consisting of 337 parts by weight of biphenyl-type epoxy resin "NC-3000H" (manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 275, resin solid content 80% by weight), 202 parts by weight of melamine-modified phenolic varnish resin "LA-7054" (manufactured by DIC Co., Ltd., hydroxyl value 125, resin solid content 60% by weight), 190 parts by weight of phenoxy resin "jER1256" (manufactured by Mitsubishi Chemical Co., Ltd., Mw≈48,000, Tg 95℃, resin solid content 100% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazole.
[0079] (Comparative Example 2) A resin varnish with a resin solid content of 40% by weight was prepared by adding a mixed solvent of γ-butyrolactone / cyclohexanone as a solvent to a mixture consisting of 347 parts by weight of dicyclopentadiene-type epoxy resin "HP-7200H" (manufactured by DIC Corporation, epoxy equivalent 283, resin solid content 80% by weight), 183 parts by weight of melamine-modified cresol phenolic varnish resin "EXB-9854" (manufactured by DIC Corporation, hydroxyl value 151, resin solid content 80% by weight), 290 parts by weight of soluble polyimide resin (synthesis example 1, resin solid content 20% by weight), 303 parts by weight of phenoxy resin ERF-001M30 (manufactured by Nippon Steel Epoxy Manufacturing Co., Ltd., Tg 146°C, resin solid content 30% by weight), 57 parts by weight of phosphazene derivative "FP-100" (manufactured by Fushimi Pharmaceutical Co., Ltd.), and 0.7 parts by weight of 2-ethyl-4-methylimidazolium.
[0080] Using the resin varnish of Comparative Examples 1-2, double-sided copper foil FCCLs and single-sided copper foil FCCLs were produced by operating in the same manner as in Examples 1-6.
[0081] (Comparative Examples 3-5) The following FCCLs are used as commercially available products: Comparative Example 3: Commercially available 2-layer FCCL cast by casting; Comparative Example 4: Commercially available 2-layer FCCL laminated product; Comparative Example 5: Commercially available 3-layer FCCL.
[0082] (Evaluation of various characteristics) The double-sided copper foil FCCL prepared using the above-described procedure was evaluated for peel strength, solder heat resistance, and dimensional stability. The film obtained by etching the entire double-sided copper foil FCCL was used to evaluate Tg and CTE using the TMA (thermomechanical analysis) method. The test methods were based on JIS C 6471.
[0083] Furthermore, warpage was evaluated on single-sided copper foil FCCLs prepared using the above procedure. Specifically, samples cut to 100mm x 100mm were placed on a mirror plate with the copper foil side facing upwards, and their float was measured. A float of less than 5mm was considered to be no warpage. Additionally, the entire copper foil was etched, and floatpage was similarly measured.
[0084] (Tensile modulus and Tg of adhesive film) The tensile modulus and Tg of the films made from the resin varnishes (adhesive compositions) prepared in Examples 1-6 and Comparative Example 1 were determined by the following method.
[0085] A resin varnish (adhesive composition) was applied to the glossy surface of an 18 μm electrolytic copper foil using a bar coater and dried at 150°C to produce a semi-cured (B-state) copper foil with adhesive (adhesive thickness: approximately 21 μm). The volatile content of the solvent was adjusted to 0.6 wt%. The glossy surface of the 18 μm electrolytic copper foil was stacked on the surface of the adhesive sheet of the copper foil with adhesive, and the sheet was placed in a vacuum press and heated / pressurized at 180°C for 90 minutes at 1 MPa (vacuum degree 5 torr) to form the film. Then, the tensile modulus and Tg were measured for the approximately 20 μm adhesive film obtained by etching the entire surface of the copper foil. Tensile modulus was determined according to IPC-TM-650-2.4.18.3. A 10mm wide strip sample was placed in a tensile / compression testing machine with a 50mm gap between clamps. Tensile strength was measured at a tensile speed of 50mm / min and calculated based on the relationship between tensile stress and strain. Tg was determined according to IPC-TM-650-2.4.24.3. Both IPC-TM-650-2.4.18.3 and IPC-TM-650-2.4.24.3 were performed according to the methods described in "IPC-TM-650 TEST METHODS MANUAL".
[0086] The composition and performance evaluation results of the FCCLs of Examples 1-6 and Comparative Examples 1-5 are shown in Tables 1-4 below.
[0087] [Table 1] [Table 2] [Table 3] [Table 4] As shown in Tables 1-4, the FCCLs (Examples 1-6) produced using the adhesive of the present invention exhibit improved dimensional stability compared to the FCCL (Comparative Example 1) produced using an adhesive with a phenoxy-modified epoxy resin and a film Tg below 120°C. No warping of the single-panel was observed. Furthermore, when using an adhesive with a phenoxy resin having a Tg exceeding 120°C, the polyimide film and copper foil could not bond at a lamination temperature of 100°C, making lamination impossible. Copper foil breakage occurred at a lamination temperature of 125°C (Comparative Example 2). Moreover, it is evident that the FCCLs of Examples 1-6, despite being produced using a lamination process, achieve the same characteristics as the commercially available cast 2-layer FCCL (Comparative Example 3).
[0088] Industrial practicality By using the adhesive and adhesive sheet of the present invention, a flexible copper clad laminate (2.2-layer FCCL) can be provided that has the same properties as a cast 2-layer FCCL and a higher productivity than a laminated 2-layer FCCL.
Claims
1. An adhesive for bonding a polyimide film substrate and a copper foil constituting a flexible copper-clad laminate, the adhesive comprising: a solvent-soluble polyimide having repeating units represented by the following general formula [I], a phenoxy resin having a glass transition temperature Tg of 90°C or higher and 120°C or lower, an epoxy resin, and an epoxy resin curing agent. In the formula, Z is an aromatic or alicyclic tetracarboxylic dianhydride residue, and Ar is an aromatic diamine residue with a phenylindanate structure.
2. The adhesive according to claim 1, wherein, The tensile modulus of the film obtained by heating and curing the semi-cured film made of the adhesive at 180°C for 90 minutes is 1 to 10.0 GPa, and the Tg is 120 to 190°C.
3. The adhesive according to claim 2, wherein, The glass transition temperature (Tg) of the phenoxy resin is 90–110 °C.
4. The adhesive according to any one of claims 1 to 3, wherein, The adhesive contains a solvent-soluble polyimide resin solid component in a weight ratio of 1:1.2 to 12.0 to phenoxy resin.
5. The adhesive according to any one of claims 1 to 3, wherein, The total content of solvent-soluble polyimide resin and phenoxy resin is 10 to 50% by weight relative to the total content of solvent-soluble polyimide resin, phenoxy resin, epoxy resin and epoxy resin curing agent contained in the adhesive.
6. An adhesive sheet, which is an adhesive sheet for flexible copper-clad laminate formed by laminating an adhesive layer for bonding copper foil on one or both sides of a polyimide film substrate constituting a flexible copper-clad laminate, wherein the adhesive layer contains the adhesive according to any one of claims 1 to 5.
7. The adhesive sheet according to claim 6, wherein, The tensile modulus of the film obtained by heating and curing a semi-cured film made of the adhesive at 180°C for 90 minutes is lower than that of the polyimide film substrate.
8. The adhesive sheet according to claim 6 or 7, wherein, The thickness of the adhesive layer is 1.6–4.0 μm.
9. The adhesive sheet according to claim 6 or 7, wherein, The adhesive sheet is an adhesive sheet with a thickness of 1.5 to 3.5 μm when the adhesive sheet is heated and cured at 180°C for 90 minutes.
10. A flexible copper-clad laminate, which is formed by sequentially laminating an adhesive layer and copper foil on one or both sides of a polyimide film substrate, wherein the adhesive layer contains the adhesive according to any one of claims 1 to 5.
11. The flexible copper-clad laminate of claim 10, wherein, The thickness of the copper foil is 1.5 to 18 μm.
12. The flexible copper-clad laminate of claim 10 or 11, wherein, The surface roughness Rz of the copper foil surface in contact with the adhesive layer is lower than the thickness of the adhesive layer.
13. A method for manufacturing the flexible copper-clad laminate according to any one of claims 10 to 12, the method comprising: The copper foil layer is pressed onto the adhesive sheet according to any one of claims 6 to 7 at a temperature of 70 to 120°C, and then the adhesive layer is cured at a temperature below 200°C.
Citation Information
Patent Citations
Single-sided flexible copper plated board for lamination
JP1994232553A
Copper clad flexible circuit board and its manufacturing method
JP2002280684A
Copper-clad sheet for protection against heat
JP2003071982A
Flexible copper-clad laminated sheet
JP2003136631A
Thermosetting resin composition, resin film, and film-attached product
JP2006328214A